MCE‐electrochemical detection for following interactions of ssDNA and dsDNA with methylene blue - Castaño‐Álvarez, Mario (Electrophoresis, 2009)
The interaction between the organic dye, methylene blue and DNA has been studied by MCE with electrochemical detection. Interaction produces two different signals, one corresponding to free methylene blue and other, for the complex methylene blue–DNA. The hybridization between a ssDNA and a complementary sequence, specific to the severe acute respiratory syndrome virus, has been performed and studied in a thermoplastic olefin polymer of amorphous structure CE‐microchip with an end‐channel gold wire detector. Moreover, studies with a longer dsDNA, an expression vector involved in the transitory or stable expression in mammals cells, pFLAG‐CMV4, has also been performed.